2009
DOI: 10.1523/jneurosci.5852-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortex Bilateral Motor Representation Depends on Subcortical and Interhemispheric Interactions

Abstract: The corticospinal tract is a predominantly crossed pathway. Nevertheless, the primary motor cortex (M1) is activated bilaterally during unilateral movements and several animal studies showed that M1 has a bilateral motor representation. A better understanding of the uncrossed corticospinal system is especially important for elucidating its role in recovery of limb control after unilateral injury. We used intracortical microstimulation (ICMS) to determine the representation of contralateral and ipsilateral fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
88
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 51 publications
10
88
1
Order By: Relevance
“…Since a parallel increase was observed in the extent of motor representations, it can be concluded that recovery of M1 output occurred through corepresentation of contralateral and ipsilateral movements at the same cortical site. Indeed, ipsilateral movement representation in M1 might be an important component of recovery in hemipakinsonian rats, as after unilateral damage of the pyramidal system (Brus-Ramer et al, 2009). Moreover, consistent with previous reports that behavioral changes after unilateral nigrostriatal degeneration are not restricted to the contralateral paw (Vergara-Aragon et al, 2003;Miklyaeva et al, 2007;Woodlee et al, 2008), we found a bilateral decrease in the distal-to-proximal ratio of forelimb representations.…”
Section: Discussionsupporting
confidence: 92%
“…Since a parallel increase was observed in the extent of motor representations, it can be concluded that recovery of M1 output occurred through corepresentation of contralateral and ipsilateral movements at the same cortical site. Indeed, ipsilateral movement representation in M1 might be an important component of recovery in hemipakinsonian rats, as after unilateral damage of the pyramidal system (Brus-Ramer et al, 2009). Moreover, consistent with previous reports that behavioral changes after unilateral nigrostriatal degeneration are not restricted to the contralateral paw (Vergara-Aragon et al, 2003;Miklyaeva et al, 2007;Woodlee et al, 2008), we found a bilateral decrease in the distal-to-proximal ratio of forelimb representations.…”
Section: Discussionsupporting
confidence: 92%
“…Several authors have showed that although the main organizational principle of primate motor systems is cortical control of contralateral limb movements, motor areas also appear to play a role in ipsilateral limb movements. [48][49][50] Numerous studies have also presented evidence that after unilateral damage, the ''contralesional'' intact hemisphere plays an increased role in ipsilateral movements and that the intact contralesional hemisphere may play a maladaptive role under certain conditions. 51 Approximately 15% in the normal population should be regarded as anastomosis, connections, or neurorrhaphies between median and ulnar nerve at the forearm named as Martin-Gruber connections.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, after a large stroke, tissue with similar function may only be found at more distant sites, such as the premotor cortex (for motor cortex stroke) (8,9) or regions within the unaffected contralateral hemisphere (10) where structural remodeling can be observed (11). Although the canonical view of sensory and motor processing is that body parts are controlled by neurons in the cerebral hemisphere on the opposite side of the body, ipsilateral pathways in which, for example, the right hemisphere processes information from the right side of the body are also present (12,13) and may provide a means to recovery. Evidence suggests that stroke recovering animals and patients can exhibit widespread changes in activity patterns that can even extend to the unaffected hemisphere (14)(15)(16).…”
mentioning
confidence: 99%